Clinical health conditions in the elderly submitted to upper and lower limb amputation (Research, Society and Development, 2021)
Introduction: Amputation is the removal of a limb or a segment of it, which can be larger or smaller depending on the affected site, and the presence of comorbidities such as diabetes and hypertension are considered risk factors for its realization. Objective: To know what are the most prevalent clinical health characteristics in elderly patients undergoing amputations in a reference service, in order to help in the development of health actions to better serve this population. Methodology: This is a descriptive, quantitative, retrospective cross-sectional study, carried out with 418 elderly amputees in a large hospital located in the city of Recife (PE). Results: The most prevalent comorbidities in the studied sample were Systemic Arterial Hypertension (SAH) (83.7%), Diabetes Mellitus (DM) (83.3%), ex-smoking (37.0%), smoking (28.5 %) and kidney disease (28.1%). Right Lower Limb Critical Ischemia (ICMID) (31.5%), Left Lower Limb Critical Ischemia (ICMIE) (28.3%) and wet gangrene (14.4%) were the main causes of amputation. Conclusion: It is hoped that the study can support the development of educational and preventive strategies, as well as contribute to actions that can be directed to this audience in order to maintain adequate care focused on the control and treatment of the causal factors of amputations, aiming to improve the quality of life.